Mejores prácticas para la gestión de proyectos eficientes en empresas constructoras Mipyme bajo la metodología PMBOK (2017)
The Colombian construction companies MYPIMES, have been developing projects without a management structure that allows them to carry out an evaluation assessment of the projects executed, leading to terminations with delays in delivery, costs, absence of direction and deficiencies in the general planning of the projects. same. Likewise, the construction company MIPYME, with more than 10 years of experience in the market and made up of professionals and departments, has not been the exception, since it has carried out institutional projects at a national level and, like other companies, has not counted with a project management.